Patients' perspectives on the medical primary–secondary care interface: systematic review and synthesis of qualitative research. Issue 10 (15th October 2015) - Sampson, Rod; Cooper, Jamie; Barbour, Rosaline; Polson, Rob; Wilson, Philip
Abstract : Objectives: To synthesise the published literature on the patient experience of the medical primary–secondary care interface and to determine priorities for future work in this field aimed at improving clinical outcomes. Design: Systematic review and metaethnographic synthesis of primary studies that used qualitative methods to explore patients' perspectives of the medical primary–secondary care interface. Setting: International primary–secondary care interface. Data sources: EMBASE, MEDLINE, CINAHL Plus with Full text, PsycINFO, Psychology and Behavioural Sciences Collection, Health Business Elite, Biomedica Reference Collection: Comprehensive Library, Information Science & Technology Abstracts, eBook Collection, Web of Science Core Collection: Citation Indexes and Social Sciences Citation Index, and grey literature. Eligibility criteria for selecting studies: Studies were eligible for inclusion if they were full research papers employing qualitative methodology to explore patients' perspectives of the medical primary–secondary care interface. Review methods: The 7-step metaethnographic approach described by Noblit and Hare, which involves cross-interpretation between studies while preserving the context of the primary data. Results: The search identified 690 articles, of which 39 were selected for full-text review. 20 articles were included in the systematic review that encompassed a total of 689 patients from 10 countries. 4 important areas specific to the primary–secondary care interface from the patients' perspective emerged: barriers to care, communication, coordination, and 'relationships and personal value'. Conclusions and implications of key findings: Patients should be the focus of any transfer of care between primary and secondary systems. From their perspective, areas for improvement may be classified into four domains that should usefully guide future work aimed at improving quality at this important interface. Trial registration number: PROSPERO CRD42014009486.